TI_GERICHTE 11.2012.119 vom 18. Dezember 2014 , Alienazione dell'oggetto litigioso in pendenza di causa: effetti - TI Tribunale d'appello (2014)
Alienazione dell'oggetto litigioso in pendenza di causa: effetti